Vitiate of Traffic and Transportation on Roads and Regulatory Measures: Addressing Challenges in Traffic and Transportation Management (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the last century, there have been vast improvements in the living conditions and economic wealth of the industrialized nations of the world and, as a result, large population growth, particularly in urban areas. The growth of cities and towns has also led to an increase in the need for mobility and the volume of vehicles occupying road infrastructure. Statistics indicate that the volume of road traffic has increased threefold over the last 30 years and that the number of road fatalities has decreased by half. However, the increase in the number of vehicles far exceeded the expected capacities and adaptive capabilities of the existing road infrastructure, particularly in large cities, leading to a deterioration in traffic performance and increasing difficulties in maintaining an acceptable and sustainable safety standard. This situation calls for better use of the existing road infrastructure and has highlighted the role of transport planning and road engineering as a means of optimizing and balancing the key objectives of the traffic system concerned with safety, accessibility, capacity, performance and environmental issues and meeting the needs and demands of the various road user groups, given the limited resources available.